RANCANG BANGUN DAN UJI PROTOTIP GENERATOR MAGNET PERMANEN 1kW/48 V MENGACU PADA STANDAR IEC 60034-4 - Muhammad Kasim; Fitriana Fitriana; Pudji Irasari (Badan Standardisasi Nasional, 2009)
This paper discusses on the designing, construction and testing of the low-speed generator prototype for batterycharging refer to the international standard documents. The specification of generator is 3 phase, 1 kW, 48 V, 18poles, 300 rpm, using permanent magnet NdFeB with remanence flux density of 1 Tesla. The design is validatedby testing the prototype to find out the power curve generated and the efficiency at loading condition. The otheranalysis is conducting the no-load characteristic to find out the prototype parameter conformity with the design.The test result shows that generator is able to produce voltage of 83,2 volt and output power of 596,9 watt at 300rpm and tested efficiency 43%.